Strategické a marketingové plánování ve stavebním podniku - Mór, Kryštof (Vysoké učení technické v Brně. Fakulta stavební, 2021)
Hlavním cílem bakalářské práce je teoreticky popsat strategické a marketingové plánování ve stavebním podniku a následně tyto získané poznatky z části teoretické, aplikovat v části praktické, při tvorbě marketingového plánu pro konkrétní stavební společnost.

The main aim of this bachelor thesis is to theoretically describe strategic and marketing planning in a construction company and this knowledge from theoretical part, apply in the practical part, in creating a marketing plan for specific construction company.
Strategic and marketing planning in a construction company
Keywords: Strategické plánování; marketingové plánování; SWOT analýza; SLEPTE analýza; Porterova analýza; marketingový cíl; specifické cíle; marketingový mix; zákazníci; segmentace; targeting; positioning; marketingový plán; Strategic planning; marketig planning; SWOT analysis; SLEPTE analysis; Porter´s analysis; marketing goal; specific goals; marketing mix; customers; segmentation; targeting; positioning; marketing plan